Parallel algorithms for LU decomposition on a shared memory multiprocessor - Kaya, Dogan; Wright, Ken (Applied mathematics and computation, 2005)
In this work, we present the numerical results (using C++) obtained from seven different versions of the LU decomposition algorithms. Four of the algorithms use Crout-like reduction and three of the algorithms use Doolittle-like reduction.